Twin liquid crystals and segmented thermotropic polyesters containing azobenzene?effect of spacer length on LC properties - Nardele, Chinmay G.; Asha, S. K. (Journal of Polymer Science Part A: Polymer Chemistry, 2012)
We report systematic studies on a homologous series of twin liquid crystalline (LC) molecules based on phenyl and naphthyl azobenzene (PnP and NpnNp) as well as segmented copolyesters based on them. The twin series had the structure azobenzene–oligooxyethylene–azobenzene, where the ethyleneoxy length was varied from 2 to 6 units. The LC properties of the twin series depended on the chemical structure of the azochromophore and also the length of the central oligooxyethylene segment. The PnP series exhibited smectic LC properties for n > three oligooxyethylene units. Conversely, NpnNp series exhibited spherulitic phases only for the shortest member –Np2Np. One non-LC short spacer twin (P2P) and one LC long spacer twin (P6P) were incorporated as part of a main chain polyester composed of fully aliphatic segments of sebacate and di or tetraethylene glycol (DEG/TEG) units by melt polycondensation. Non-LC P2P formed LC polymers even at low (5 mol %) incorporation in DEG-based copolymers, whereas the LC-P6P could do so only at 30 mol % incorporation. The LC properties of the twin molecules as well as copolymers were studied using differential scanning calorimetry, polarized light microscopy (PLM) along with variable temperature wide angle X-ray diffraction. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012

Temperature sensitive emission color tuning and white light emission in segmented OPV polymer: perylene bisimide supramolecular complex - Shinde, Shekhar; Asha, S. K. (Macromolecules, 2016)
An oligo(phenylenevinylene) (OPV) based segmented polymer (POPV) and its small molecule model compound (SOPV) were designed with a carboxyl functionality in the side chain. The polymer and small molecule were complexed with pyridine functiorialized perylene bisimide (UPBIPy) and the properties of the donor: acceptor (D:A) complexes were compared. Both polymer and small molecule D:A complexes formed lamellar morphologies in the <10 nm length scale, which could be visualized by TEM and AFM imaging. The flexibility of the segmented polymer architecture imparted special properties to the polymer and its complex. The polymer complex (POPVC) exhibited white light emission with CIE color coordinates (0.27, 0.32) due to partial energy transfer from POPV to UPBIPy. The analogous model OPV complex (SOPVC) continued to show characteristic blue OPV emission in the complex also. The higher sensitivity of polymers toward temperature was made use of to tune the emission color in the complex from white (0.27, 0.32) at 30 degrees C to yellow-green (0.29, 0.31) at 100 degrees C and back to white (0.27, 0.31) upon cooling to 30 degrees C. Such a temperature sensitive emission color tuning was not observed in the small molecule complex under identical conditions.

Thiol-ene-based degradable 3D printed network from bio resource derived monomers ethyl-lactate and isosorbide - Pal, Shibam; Asha, S. K. (European Polymer Journal, 2024)
A polymeric ene-based thiol-ene network is reported that was demonstrated for light-based 3D printing. Allyl poly (acrylate ethyl lactate) (PAEL) was synthesized starting from ethyl lactate in an efficient and scalable manner. Ethyl lactate is a biobased material obtained naturally or chemically in high yields in the form of ethyl ester of lactic acid. Isosorbide, which is also a bio based resource was converted into thiol derivative and was used along with Pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) as multifunctional thiol. The polymeric nature of the ene (i.e. PAEL) imparted exceptionally high mechanical properties like Young's modulus of 1.75 GPa as well as high thermal stability with a decomposition temperature (Td,10%) exceeding 350 C for all the networks studied. The properties could also be customized by fine tuning the type and stoichiometric ratio of the thiol crosslinked employed. For instance, the Young's modulus range from 1.75 GPa to 1.03 GPa and glass transition temperature range from 44 C to 54 C could be achieved. DLP 3D printing was used to demonstrate the printability of the resins with high resolution and structural fidelity. The study also highlights the basemediated rapid hydrolytic degradation efficiency of the 3D printed parts, demonstrating the applicability of these novel polymeric ene based thiol-ene for sustainable and eco-friendly 3D printable formulations.
Keywords: 3D printing; Degradation; digital light processing; Poly (acrylate ethyl lactate); Thiol-ene